Performance of steers limit-fed in drylot or on mature native pasture - F.K. Brazle; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1990)
Growing steers were limit-fed the same amount of a grain- and silage-based ration either in drylot or on dormant native range. The steers wintered on pasture gained 14.2% slower (1.82 V5 2.08 lb/d; P<.01) and were 15.3% less efficient than those in drylot, apparently because of increased energy expenditure from voluntary exercise.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Mature grass; Drylot; Growing; Limit feeding